Common challenges in teaching initiation: narratives of young public high school teachers - Leal, Álida Angélica Alves; Leão, Geraldo Magela Pereira (Debates em Educação, 2026)
This article analyzes the experiences of young beginning teachers in public high schools with the purpose of identifying and understanding some common challenges to this group. Young people were considered to be those up to 29 years of age, and beginning teachers were those with 5 years or less of experience in the profession. The methodological approach consisted of conducting, transcribing and analyzing 25 narrative interviews with young beginning teachers who taught in state public high schools located in a region of Belo Horizonte, Minas Gerais, in addition to the application of questionnaires. The experiences narrated were analyzed based on analytical categories from Sociology of the Individual, the Sociology of Experience and discussions on teaching status and initiation into teaching.One of the most acute common challenges identified from the narratives concerns entry and survival in the job market. Data processing allowed us to visualize the career paths and perspectives of young beginning teachers when facing the intersections of two sets of dilemmas or tensions: to remain or abandon teaching in basic education and, also, to reconcile or not teaching with the exercise of other professions. Four categories of analysis were defined: a) desire to remain in teaching for a long time (career); b) perspective of continuing in teaching, however, based on reconciliation with work in another area (simultaneous pluriactivity); c) hesitation regarding remaining in or leaving teaching (uncertainty); and d) perspective of abandoning the profession (sequential pluriactivity).